2022
DOI: 10.1111/jerd.12972
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for professional dental bleaching using a polymeric catalyst primer

Abstract: Objective: Evaluate the influence of a polymeric catalyst primer (PCP) on esthetic efficacy (EE), degradation kinetics of hydrogen peroxide (H 2 O 2 ), and transamelodentinal cytotoxicity (TC) of bleaching gels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
(172 reference statements)
0
6
0
Order By: Relevance
“…Then, 16 studies were excluded, and the reasons for their exclusion can be found in Figure 1 and Supplementary Data 1 [ 32 33 34 35 36 37 38 39 40 41 42 43 44 ]. Twenty-seven studies meeting the inclusion criteria were selected for qualitative analysis [ 1 3 6 11 12 17 23 24 25 26 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Then, 16 studies were excluded, and the reasons for their exclusion can be found in Figure 1 and Supplementary Data 1 [ 32 33 34 35 36 37 38 39 40 41 42 43 44 ]. Twenty-seven studies meeting the inclusion criteria were selected for qualitative analysis [ 1 3 6 11 12 17 23 24 25 26 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of these studies utilized human dental pulp cells (HDPCs) and mouse dental papilla Cell-23 (MDPC-23) cells, with each cell type being used in 10 studies. Of these, 8 studies employed enamel/dentin discs in conjunction with pulp cells, while the remaining studies used extracts from bleaching gel [ 6 23 45 47 57 59 60 62 ]. The bleaching gel most frequently evaluated was the HP-based gel, which was used in varying concentrations and volumes, and applied over periods ranging from 15 minutes to 12 days [ 23 24 45 46 48 49 50 51 52 53 54 55 56 57 59 60 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations